Postcards in the Porfirian Imaginary - Osorio, Alejandra Betilde (Social justice, 2007)
Part of a special issue on the relationship between art, identity, and social justice. The writer examines the development of postcards during the dictatorship of Porfirio Díaz in Mexico, 1877–1911. She observes that the postcards produced in Mexico during this period contained definitively ideological content and helped to solidify national consciousness toward the end of the 19th century, during the consolidation of the Mexican state; they reflect the edifying feeling of a culture and nation that succeeded in structuring a national discourse centered around the notion of progress. However, she notes, at the same time, foreign photographers and editors created popular representations of Mexico and Mexicans, in which they depicted the “traditional” culture as premodern.